2020
DOI: 10.3390/ijerph17155443
|View full text |Cite
|
Sign up to set email alerts
|

Association between Compliance with the 24-Hour Movement Guidelines and Fundamental Movement Skills in Preschoolers: A Network Perspective

Abstract: The present study aimed to analyze the compliance with the 24-h movement guidelines and its association with fundamental motor skills (FMS) in early childhood, considering sex and Body Mass Index (BMI) in a network perspective. Two hundred and twelve preschoolers (109 boys, 4.45 ± 0.78 years old) provided physical activity (PA), sleep duration, screen time, fundamental motor skills (FMS) and BMI data. Relationships between compliance with movement behaviors guidelines, FMS, sex and BMI were calculated using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…The direction of this relationship was not expected because we hypothesized sedentary behavior to be a negative predictor of motor competence. When considering the literature, a recent cross-sectional study (Martins et al, 2020) in Brazilian children using network analysis (and considering other relevant factors such as BMI and physical activity) also reported a positive relationship between screen time using a similar parent proxy report measure as the present study (total average duration of TV, computer, and videogames) and locomotor and object control skills for 3-year-olds. However, authors of this study reported that in 4-and 5-year-olds, this association was negative and stronger (Martins et al, 2020).…”
Section: Discussionsupporting
confidence: 60%
“…The direction of this relationship was not expected because we hypothesized sedentary behavior to be a negative predictor of motor competence. When considering the literature, a recent cross-sectional study (Martins et al, 2020) in Brazilian children using network analysis (and considering other relevant factors such as BMI and physical activity) also reported a positive relationship between screen time using a similar parent proxy report measure as the present study (total average duration of TV, computer, and videogames) and locomotor and object control skills for 3-year-olds. However, authors of this study reported that in 4-and 5-year-olds, this association was negative and stronger (Martins et al, 2020).…”
Section: Discussionsupporting
confidence: 60%
“…From a network perspective, we can better understand connections between variables in a complex system. Indeed, to facilitate a better understanding of the collective impact of 24-hour movement behaviors on health, researchers have begun to introduce network analysis into this field [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the importance of these movement behaviors for health is evident, reports from several countries worldwide have shown that less than 15% of preschool-aged children are compliant with the three recommendations of the WHO guidelines. [10][11][12] In Brazilian preschoolers, this adherence is markedly lower 13 and may compromise children´s short and long-term health.…”
mentioning
confidence: 99%